2016
DOI: 10.1111/1475-6773.12462
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Hospital Nurse Staffing and Patient Experience with Care: Differences between Cross‐Sectional and Longitudinal Estimates

Abstract: After controlling for unobserved hospital characteristics, the positive influences of increased nurse staffing levels and skill mix were relatively small in size and limited to a few measures of patients' inpatient experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 42 publications
8
47
0
Order By: Relevance
“…This study showed that, overall, patients were satisfied with the nursing care they received, and more satisfied when the proportion of baccalaureate nurses in the nursing workforce was higher. These results support findings of previous studies (You et al., ); nevertheless, clear evidence correlating hospital nurse staffing with patient satisfaction is limited (Aiken et al., ; Ball, Griffiths, & Hope, ; Laal, ; Martsolf et al., ). Surprisingly, the highly demanding medical unit with the lowest quantity of required registered nurses had the most satisfied patients.…”
Section: Discussionsupporting
confidence: 90%
“…This study showed that, overall, patients were satisfied with the nursing care they received, and more satisfied when the proportion of baccalaureate nurses in the nursing workforce was higher. These results support findings of previous studies (You et al., ); nevertheless, clear evidence correlating hospital nurse staffing with patient satisfaction is limited (Aiken et al., ; Ball, Griffiths, & Hope, ; Laal, ; Martsolf et al., ). Surprisingly, the highly demanding medical unit with the lowest quantity of required registered nurses had the most satisfied patients.…”
Section: Discussionsupporting
confidence: 90%
“…The limitation of our present work with regard to mediation modeling is the cross‐sectional nature of our data, which does not allow us to claim temporal precedence required in the definitions of mediators and moderators as could be inferred from a longitudinal study. However, in previous research (Martsolf et al) results from cross‐sectional studies coincided with results from longitudinal studies. Therefore, we expect that the estimates of the relevant coefficients would not change drastically if based on a longitudinal study.…”
Section: Discussionsupporting
confidence: 65%
“…The authors used Cox proportional hazards regression models to determine increased risk of mortality after periods of exposure to low nurse staffing (Needleman et al). A recent longitudinal study assessing the association between nurse staffing and patient experiences largely confirmed findings from cross‐sectional studies (Martsolf et al). Although the RN4CAST data have a cross‐sectional nature, with the same data as used in this study, it was illustrated that 2 elements in the organization of nursing care, better nurse staffing, and better nurse working environments are associated with better patient experiences and lower patient mortality (Aiken et al and Aiken et al).…”
Section: Rn4cast Study and Research Questionssupporting
confidence: 57%
“…; Martsolf et al. ). Indeed, patients’ self‐reported experience with hospital care (i.e., patient experience of care) has become a widely used type of quality measure.…”
mentioning
confidence: 97%
“…; Kang ), although a recent study by Martsolf et al. () suggests that this relationship may at least in part be attributable to hospital characteristics that are not readily measurable but likely to influence both nurse staffing patterns and the quality of patient care (Jha et al. ; Kutney‐Lee et al.…”
mentioning
confidence: 99%